PENGARUH KEPEMIMPINAN, KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN (StudiPada PT Sango Ceramics Indonesia Semarang) - YovinaRiskitasariSusilo, 13.05.51.0092 (Students' Journal of Economic and Management, 2017)
This research aims to analyse the influence of leadership, compensation and motivation of work against employee performance of PT. Sango Ceramics Indonesia Semarang. The data used are primary data obtained direcly from the original source in the form of a questionnaire. The population in this study were employee of PT. Sango Ceramics Indonesia Semarang numbering as many as 1000 people. The sampling technique in this study used purposive kind of accidental sampling method with the number respondents as many as 100 people. The results of the analysis can be concluded that: (1) leadership has a positive and significant influence on employee performance. (2)Compensation has a positive and significant influence on employee performance. (3) Motivation has a positive and significant influence on employee performance. Keywords: leadership, compensation, motivation and employee performance